Salaries and Work Effort: An Analysis of the European Union Parliamentarians. (28th October 2013) - Mocan, Naci; Altindag, Duha T.
<x xml:space="preserve">Abstract</x> Before July 2009, salaries of the Members of the European Parliament (MEPs) were paid by their home country, and there were substantial salary differences between MEPs representing different countries. Starting in July 2009, salaries are pegged to 38.5% of a European Court judge's salary, paid by the European Union. This created an exogenous change in salaries, the magnitude and direction of which varied substantially. Using information on each MEP between 2004 and 2011, we show that an increase in salaries decreases attendance at plenary sessions and reduces the number of questions asked but it has no impact on other job‐related activities.